Z‐axis video for cytology database is a useful tool for the case presentation prior to the cytology training workshop. Issue 1 (27th June 2011) - Yamashiro, Katsushige; Shinohara, Toshiya; Mitsuhashi, Tomoko; Sugimura, Takuya; Taira, Kiyomi; Azuma, Manabu; Okuyama, Dai; Nakajima, Manami; Takeda, Hiroko; Suzuki, Hiroaki
Abstract We have built a database on the Internet managing z‐axis video for cytology (Zavic), and report on a new style of case discussion supported by the Zavic database. Z‐axis video for cytology is a movie file derived from the video recording of a microscopic field with changes in the focus. We used it for the case presentation of EUS‐FNA of pancreatic lesions on the Internet prior to a training workshop. The attendees were asked to observe the Zavic and to make diagnoses of 20 cases before the workshop. Fourteen attendees also observed lesions under a microscope on that day, and the results were compared with those of Zavic observation. The evaluation of the Zavic database (DB) was surveyed by a questionnaire. The average number of accurate diagnoses by 46 Zavic observers was 10.8. These accuracies for those who observed both the Zavic and glass slides were 11.57 and 11.43, respectively, for the videos and slides. Compared with Zavic observation alone, the diagnoses with glass slide observation were shifted to a correct diagnosis in two cases, but were shifted to an incorrect diagnosis in two cases. Approximately 60% of Zavic observers replied in the questionnaire that the movies on Zavic DB started to play within 3–4 seconds after clicking the play button. We successfully carried out the new style of case discussion supported by the Zavic DB. It was evaluated favorably by many attendees, who were psychologically still dependent on the glass slide observation. Diagn. Cytopathol. 2013. © 2011 Wiley Periodicals, Inc.